Keterikatan (Klitik) Pronomina Persona dalam Bahasa Indonesia - Icuk Prayogi (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Bahasa Indonesia has two types of pronouns: bound pronouns and free pronouns. The entanglement of its form is not only based on the contraction that occurs in the full words that cause the occurence of simple clitics, but it is also prominent to review the entanglement based on the syntactic structure and its prevalence. The problem is on the justification of this on the justification of this linguistic unit. If a linguistic unit has been justified as a bound pronoun is indeed a free form (free pronoun), and certain syntactic environtment will enable the free pronoun to be clitic. Therefore, the simple paper will attempt to analize the entanglement of pronouns based on phonological characteristics and syntactic analysis.